Determinant Factors Affecting Customer Satisfaction (Study on Kafa Mart Kalibeber Consumers in Wonosobo Regency) - Saqinna, Az Zahra Agni; Arifa, Ziida; Nabila; Trihudiyatmanto, M. (UM Purwokerto Press, 2025)
The purpose of this study is to examine how various factors impact customer satisfaction factors at Kafa Mart Kalibeber, specifically focusing on price, product quality, and service quality. Students and the general public who have made transactions at The research population consists of Kafa Mart Kalibeber. This study employs a quantitative method and utilizes a non-probability sampling technique, involving a total of 100 respondents. The collected data was processed and examined implementing multiple regression analysis and data processed through the use of SPSS V. 25. The findings indicate that while service quality negatively influences customer satisfaction despite being significant, both product quality and pricing positively and significantly impact it.